A case of reading epilepsy in a patient having idiopathic generalized epilepsy - Sardana, Vijay; Jain, Pallav; Shringi, Prashant (Indian Journal of Case Reports, 2019)
Reflex seizures are defined as epileptic events that are triggered only by specific stimuli which can be external or complex internalmental processes. Reading epilepsy is one such rare form of reflex epilepsy. In primary reading epilepsy, typical attacks are jaw jerks(clicking sensation or stammering), that may evolve into GTCS if reading continues. As reading epilepsy is task-specific, they aregenerally misdiagnosed as non-epileptic and thought to be due to stress related to studies. We report the case of a young male whohave jaw jerks along with blank staring spells while reading which was misdiagnosed as pseudoseizures. This rare case highlights thiseasily treatable benign reflex epilepsy syndrome.